2012
DOI: 10.1007/s10461-012-0363-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Dimensions of Disability Experienced by Adults Living with HIV: A Structural Equation Model Analysis

Abstract: As individuals age with HIV it is increasingly important to consider the health-related consequences of HIV and multiple morbidities, known as disability. We assessed relationships between four dimensions of disability among adults living with HIV. We conducted a structural equation modeling analysis using data from 913 participants in the Ontario HIV Treatment Network Cohort Study to determine relationships between four latent variables of disability in the Episodic Disability Framework: physical symptoms and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Incorporating health into the priority reflected the transition of HIV into a chronic disease, and the need to adopt a more health-oriented approach and promote self-management strategies. Evidence has explored the experience of episodic disability and relationships between dimensions of disability [ 10 ],[ 42 ], however the episodic nature of disability has not been examined longitudinally. Evidence on the barriers and facilitators to employment, and importance of employment as it relates to physical and mental health, has articulated the need for rehabilitation interventions, programs and policies to enhance the ability to recruit and retain people living with HIV in the employment sector [ 43 ]-[ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating health into the priority reflected the transition of HIV into a chronic disease, and the need to adopt a more health-oriented approach and promote self-management strategies. Evidence has explored the experience of episodic disability and relationships between dimensions of disability [ 10 ],[ 42 ], however the episodic nature of disability has not been examined longitudinally. Evidence on the barriers and facilitators to employment, and importance of employment as it relates to physical and mental health, has articulated the need for rehabilitation interventions, programs and policies to enhance the ability to recruit and retain people living with HIV in the employment sector [ 43 ]-[ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exploratory factor analysis in this study supports the notion that HIV-related stigma comprises three latent structures for adults living with HIV in Florida. [16][17][18][19][20][21][22][23][24][25] to inform the development of the 10-item scale, the scale has not been psychometrically evaluated in samples of adults living with HIV. Our work suggests that adult PLWH in Florida may report the experience of stigma differently than youth.…”
Section: Exploratory Factor Analysismentioning
confidence: 99%
“…The experience of overall HIV-related stigma was significantly associated with persons living with disability and depression. There is a small amount of work examining persons with disability and HIV-related stigma [21][22][23], which identified that stigma may exacerbate or alleviate episodes of disability. This may be because people with disabilities face significant barriers to HIV programming and services, including lack of access to health care services, sexual, or reproductive education, poverty, and challenges to social inclusion compared to those who are not disabled [24].…”
Section: Overall Stigmamentioning
confidence: 99%
“…We examined relationships between components of disability using data from the Ontario HIV Treatment Network Cohort Study (OCS) using variables that resembled dimensions of disability within the Episodic Disability Framework, such as scores from symptom and quality of life questionnaires [18]. Results from this analysis indicated that physical and mental health challenges and difficulties carrying out daily activities either directly or indirectly predicted having challenges with social participation.…”
Section: Introductionmentioning
confidence: 99%